1997
DOI: 10.1161/01.res.81.3.372
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Transduction of Nitric Oxide Synthesis in the Beating Heart

Abstract: NO alters contractile and relaxant properties of the heart. However, it is not known whether changes in ventricular loading conditions affect cardiac NO synthesis. To understand this potential contractile-relaxant autoregulatory mechanism, production of cardiac NO in response to mechanical stimuli was measured in vivo using a porphyrinic sensor placed in the left ventricular myocardium. The beating rabbit heart exhibited cyclic changes in [NO], peaking at 2.7+/-0.1 micromol/L near the endocardium and 0.93+/-0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
113
0
7

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(126 citation statements)
references
References 26 publications
6
113
0
7
Order By: Relevance
“…In mammals, myocardial stretch increases cardiac nitric oxide (NO) release from both vascular endothelium and cardiomyocytes (Pinsky et al 1997;Petroff et al 2001;Balligand et al 2009) facilitating myocardial relaxation, ventricular diastolic distensibility and hence the Starling response . In the past, the effect of NO on preload-induced increases in CO has been attributed to a paracrine effect of endothelialderived NO on myofilament Ca 2þ sensitivity secondary to troponin I phosphorylation by the cGMP-dependent protein kinase G (PKG) (Prendergast et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, myocardial stretch increases cardiac nitric oxide (NO) release from both vascular endothelium and cardiomyocytes (Pinsky et al 1997;Petroff et al 2001;Balligand et al 2009) facilitating myocardial relaxation, ventricular diastolic distensibility and hence the Starling response . In the past, the effect of NO on preload-induced increases in CO has been attributed to a paracrine effect of endothelialderived NO on myofilament Ca 2þ sensitivity secondary to troponin I phosphorylation by the cGMP-dependent protein kinase G (PKG) (Prendergast et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to measure NO levels in the whole heart have been made using electron paramagnetic resonance (Zweier et al, 1995), direct assessment of total NO release in coronary effluent using chemiluminescence (Tsukada et al, 2003) and with a NO sensitive probe (Kupatt et al, 1997) but these techniques cannot be used in conjunction with studies on electrophysiological and mechanical events during the cardiac cycle and only total NO activity is reflected. Direct beatto-beat quantification in the whole heart has been performed using a porphyrinic microsensor (Pinsky et al, 1997) but this method is technically challenging and could cause local damage limiting interpretation of data. A more practical method that allows NO to be measured in the beating heart together with simultaneous electrophysiological and mechanical events is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that systolic IMP exhibits a transmural gradient oriented from endocardium toward the epicardium (16). Accordingly, NO release was found to be higher in the endocardium than in the myocardium (19). These results clearly indicate a close relationship between the synthesis of NO and mechanical stimulation of cardiac contraction in coronary vessels.…”
Section: Discussionmentioning
confidence: 64%
“…Early studies (14), by comparing the cGMP content of platelets passing through a working or arrested heart, have demonstrated that mechanical stimulation potentiates the release of an endothelium-derived relaxing factor. More recent studies (19), by using a porphyrinic sensor placed in the left ventricular myocardium, have further demonstrated the existence of cyclic and preload-dependent changes in NO release in beating rabbit hearts. Cardiac contraction increases intramyocardial pressure (IMP), which decreases transmural pressure of coronary vessels and hence decreases the diameter of the vessels, causing enhanced shear stress and vascular deformation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation